2019
DOI: 10.1111/jon.12618
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intracranial Aneurysm Morphology and Rupture Status on the Particle Residence Time

Abstract: BACKGROUND AND PURPOSE Aneurysm hemodynamics play an important role in aneurysm growth and subsequent rupture. Within the available hemodynamic characteristics, particle residence time (PRT) is relatively unexplored. However, some studies have shown that PRT is related to thrombus formation and inflammation. The goal of this study is to evaluate the association between PRT and aneurysm rupture and morphology. METHODS We determined the PRT for 113 aneurysms (61 unruptured, 53 ruptured) based on computational fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, there is no clear consensus on the values of the trigger thresholds, and published works studying ST hemodynamic thresholds often have small sample sizes. Based on CFD simulations conducted on 113 aneurysms—where particles injected into the parent vessel were tracked over multiple cardiac cycles—Leemans et al 32 found that the particle RT for four out of five partially thrombosed aneurysms had a long RT (>1.9 s). While thrombus formation has been reported to initiate as early as RT = 1 s, 18 Marsh et al 33 found in their experiments that a threshold of RT ≥ 1 s was ineffective as multiple patients in their cohort demonstrated a median RT >1 s in the aneurysm, even before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no clear consensus on the values of the trigger thresholds, and published works studying ST hemodynamic thresholds often have small sample sizes. Based on CFD simulations conducted on 113 aneurysms—where particles injected into the parent vessel were tracked over multiple cardiac cycles—Leemans et al 32 found that the particle RT for four out of five partially thrombosed aneurysms had a long RT (>1.9 s). While thrombus formation has been reported to initiate as early as RT = 1 s, 18 Marsh et al 33 found in their experiments that a threshold of RT ≥ 1 s was ineffective as multiple patients in their cohort demonstrated a median RT >1 s in the aneurysm, even before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no clear consensus on the values of the trigger thresholds and published works studying ST hemodynamic thresholds often have small sample sizes. Based on CFD simulations conducted on 113 aneurysms-where particles injected into the parent vessel were tracked over multiple cardiac cycles-Leemans et al 21 found that the particle residence time for four out of five partially thrombosed aneurysms had a long residence time (>1.9 s). While thrombus formation has been reported to initiate as early as RT = 1 s 13 , Marsh et al 23 found in their experiments that a threshold of RT ≥ 1 s was ineffective as multiple patients in their cohort demonstrated a median RT >1 s in the aneurysm, even before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Particle residence times (PRT) were calculated by Leemans et al [19] and were correlated with morphology and the ruptured state of IAs. While morphology has an important effect on PRT, correlation with the ruptured state is insignificant.…”
Section: Introductionmentioning
confidence: 99%